Serum levels of interleukin-1α in patients with systemic sclerosis - Maekawa, Takeo; Jinnin, Masatoshi; Ohtsuki, Mamitaro; Ihn, Hironobu (Journal of dermatology, 2013)
ABSTRACT Systemic sclerosis (SSc) is an autoimmune systemic connective tissue disorder characterized by sclerotic change of the skin and multiple internal organs. Although the pathogenesis of this disorder is still unknown, overproduction of extracellular matrix proteins, including collagens and fibronectin, and aberrant immune activation may be involved in the mechanism. Interleukin (IL)‐1 is one of the key regulators of inflammatory response. IL‐1 is also involved in regulating connective tissue remodeling and cellular differentiation of epithelial and ectodermal cells. There are three major members of the IL‐1 family: IL‐1α, IL‐1β and IL‐1 receptor antagonist. IL‐1α was first described as a factor derived from keratinocytes that stimulates thymocyte proliferation. IL‐1α plays a crucial role in procollagen production by fibroblasts derived from patients with SSc. The present study was undertaken to investigate the serum levels of IL‐1α in patients with SSc. Serum samples were obtained from 66 Japanese patients with SSc and 19 healthy controls. Levels of serum IL‐1α were measured with a specific enzyme‐linked immunoassay kit. Mean serum levels were significantly higher in SSc patients than in those healthy control subjects. Moreover, contracture of phalanges was found at a significantly lower prevalence in SSc patients with elevated serum IL‐1α levels than those with normal levels. These results suggest that IL‐1α may play a role in the pathogenesis of SSc.